The Role of Marketing Mix, Market Share and E-Commerce on Business Management - Zaini, Mohamad (Dinasti Publisher, 2024)
This study aims to build a hypothesis regarding the role between variables which can later be used for further research in the scope of business management. The scientific literature review article on the role of marketing mix, share market and e-commerce on business management which is a scientific literature article in the scope of business management science. The approach used in this literature review research is descriptive qualitative. The data collection technique used in this literature article is a literature study or review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous studies relevant to this research such as academic online media including Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, one to two relevant previous articles were used to review each independent variable. The results of this literature review article are: 1) Marketing mix plays a role in Business Management; 2) Share Market plays a role in Business Management; and 3) E-Commerce plays a role in Business Management.